Assessment of administrative claims data for public health reporting of Salmonella in Tennessee. Issue Volume 22:Issue e1(2015:Apr.)Special (22nd July 2014) - Marder, Ellyn; Garman, Katie; Jones, Timothy F; Dunn, John; Jones, Stephen
Abstract: In the USA, approximately 4% of the estimated 1 million Salmonella infections occurring annually are reported to public health. Administrative claims data from large health insurance companies capture disease-specific data which could potentially enhance public health surveillance. To determine the utility of medical claims data for public health reporting of Salmonella, we assessed medical claims data from BlueCross BlueShield of Tennessee (BCBST) members compared to Tennessee Department of Health (TDH) surveillance data. BCBST Salmonella cases diagnosed during 2007–2011 were matched to TDH Salmonella cases reported during the same time period. Matches and non-matches were validated using medical records. Of the 450 BCBST cases identified, 72% matched TDH cases. All culture-confirmed BCBST cases were reported to TDH. Non-matched BCBST cases included clinical diagnoses which were culture negative or not tested. Our findings indicate administrative claims data are not currently a viable mechanism for enhancing routine reporting of Salmonella infections.